2019
DOI: 10.1039/c8nj05526b
|View full text |Cite
|
Sign up to set email alerts
|

Metal–ligand ring aromaticity in a 2D coordination polymer used as a photosensitive electronic device

Abstract: 14-Membered metal–ligand ring present in a photosensitive 2D coordination polymer, [Zn2(fum)2(4-phpy)4(H2O)2] (H2fum = fumaric acid and 4-phpy = 4-phenyl pyridine) shows aromatic character as evident by the nucleus-independent chemical shifts (NICS) calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…A comparison of the Li doped true minimum structure with the corresponding quasi-planar Al 13 + shows that now not only the lower part of the cluster but all thirteen atoms of the cluster readjusts itself and Li doped cluster is more puckered compared to the quasi-planar Al 13 + cluster. In this puckered con guration the cluster assumes a ying bird like shape with two symmetry related edges (formed by Al(5), Al(6), Al (7) and their symmetry related Al(13), Al (12) and Al( 11)) analogous to two wings, Li(1) which is placed slightly downwards of the mean plane forms the tail and three aluminium aotms (Al(8), Al (9) and Al( 10)) at the upper edge form the head portion of the cluster. An account of the bond distances and dihedral angles between adjacent triangular rings of the cluster have been provided in table 1and 4) is displaced more downward and knocked out from the bond connected by Na(1), Al(5) and Al (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the Li doped true minimum structure with the corresponding quasi-planar Al 13 + shows that now not only the lower part of the cluster but all thirteen atoms of the cluster readjusts itself and Li doped cluster is more puckered compared to the quasi-planar Al 13 + cluster. In this puckered con guration the cluster assumes a ying bird like shape with two symmetry related edges (formed by Al(5), Al(6), Al (7) and their symmetry related Al(13), Al (12) and Al( 11)) analogous to two wings, Li(1) which is placed slightly downwards of the mean plane forms the tail and three aluminium aotms (Al(8), Al (9) and Al( 10)) at the upper edge form the head portion of the cluster. An account of the bond distances and dihedral angles between adjacent triangular rings of the cluster have been provided in table 1and 4) is displaced more downward and knocked out from the bond connected by Na(1), Al(5) and Al (13).…”
Section: Resultsmentioning
confidence: 99%
“…Also Na(1) atom is located 2.46Å downward of the mean plane passing through the central Al 3 triangular core. Aluminium atoms Al(5), Al (6) and Al(7) on the left edge, as well as their symmetry related counterparts Al(13), Al (12) and Al(11) moves upward 0.54 Å, 1.95 Å and 1.52 Å respectively) of the mean plane passing through the central triangular core. This give rise to a puckered geometry of the cluster rendering the cluster a shape analogous to a ying bird with Na(1) occupying the tail region and three aluminium atoms Al(8), Al (9) and Al(10) forming the head portion of the cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminium is a cheaper material due to its higher natural abundance as well as the ease with which it can be tailored in various architectures like nano-rods [9], nano-disks [10] and nano-shells [11]. Recently Jiang et al have reported various structural possibilities for Al m B m (n=1-7 and m=1-2) using [12]. Q. L. Lu et al have reported the cage-like structure of Al 12 by DFT calculation which has revealed that the presence of Mg, Ca metals enhance the stability of the aluminium cluster signi cantly [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our group is mainly involved in the fabrication of 1D or 2D CPs, which would undergo supramolecular aggregations to from higher dimensional networks using monodonor pyridyl ligands projected from the frameworks. The supramolecular assembly offers a congenial environment toward charge transport through a space or “hopping” mechanism . Recently, efforts are being paid to fabricate suitable CPs, which show semiconducting behavior and Schottky diode application.…”
Section: Introductionmentioning
confidence: 99%